POTENCIES OF EXERCISING AGENCY AMONGST PRE-SERVICE ENGLISH TEACHERS IN MICRO TEACHING - Santi Farmasari; Baharuddin Baharuddin; Dewi Satria Elmiana; Andra Ade Riyanto; Aulia Dwi Amalina Wahab (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACTThe role of teachers as agents of learning has been echoed for decades. As a driving force in an educational institute, teachers with high agency can be analogous to critical enzymes in the body of education. However, whether or not a sense of agency has been introduced, promoted, or facilitated amongst students studying to become teachers still receives little attention. This study seeks for evidence of potencies and typology of agency amongst final year pre-service English teachers (PSETs). 199 students were facilitated to explore English learning problems in high schools and constructed problem-based lesson plans from which their agency was identified. 24 PSETs with a high degree of agency were involved in a focus group discussion. The study reveals potencies of exercising agency which were greatly informed by the PSETs’ past and present learning experiences. The agentive actions were related to the implementation of technology, better engagement, and project-based learning. By doing so, the PSETs have shown their future professional identity which is important for pre-service teacher educators and institutions. This study has important implications for pre-service teacher educators to instill and further the development of agency during their teacher education program taking into account their students’ ecological capitals and capabilities. ABSTRAKPeran guru sebagai agen pembelajaran telah digaungkan sejak lama. Sebagai penggerak di institusi pendidikan, guru dengan tingkat agensi yang tinggi dapat dianalogikan sebagai sebuah enzim krusial di dunia pendidikan. Namun, masih sangat sedikit penelitian yang mengkaji bagaimana agensi ini dapat diperkenalkan, didorong atau difasilitasi untuk berkembang pada calon guru Bahasa Inggris. Penelitian ini dilaksanakan untuk mengetahui potensi-potensi dan jenis-jenis agensi pada mahasiswa calon guru tingkat akhir. 199 mahasiswa calon guru terlibat di penelitian ini. Mereka difasilitasi untuk dapat mengeksplorasi permasalahan-permasalahan pembelajaran Bahasa Inggris sebagai dasar penyusunan rencana proses pembelajaran (RPP). 24 dari 199 dengan potensi agensi yang tinggi di RPP mereka kemudian diundang pada diskusi kelompok terfokus untuk mengklarifikasi rencana-rencana agentif mereka dalam memecahkan permasalahan pembelajaran. Penelitian ini menemukan bahwa terdapat beberapa potensi agensi pada mahasiswa calon guru Bahasa Inggris yang berorientasi pada pemanfaatan teknologi, keterlibatan aktif dalam pembelajaran dan pembelajaran berbasis proyek. Hasil penelitian ini mempunyai implikasi penting terhadap model pembelajaran calon guru di lembaga pendidik tenaga kependidikan (LPTK) untuk menanamkan dan mengembangkan agensi guru sedini mungkin dengan memberikan stimuli-stimuli yang sesuai dengan kondisi ekologi dan kapasitas mahasiswa calon guru.How to Cite: Farmasari, S. Baharuddin, Elmiana, D. S., Riyanto, A.A., Wahab, A.D.A. (2023). Potencies of Exercising Agency Amongst Pre-Service English Teachers in Micro Teaching Class. IJEE (Indonesian Journal of English Education), 10(1), 23-36. doi:10.15408/ijee.v10i1.30873